2021
DOI: 10.3389/fphys.2021.676501
|View full text |Cite
|
Sign up to set email alerts
|

Substantial and Reproducible Individual Variability in Skeletal Muscle Outcomes in the Cross-Over Designed Planica Bed Rest Program

Abstract: To evaluate the individual responses in skeletal muscle outcomes following bed rest, data from three studies (21-day PlanHab; 10-day FemHab and LunHab) were combined. Subjects (n = 35) participated in three cross-over campaigns within each study: normoxic (NBR) and hypoxic bed rest (HBR), and hypoxic ambulation (HAMB; used as control). Individual variability (SDIR) was investigated as √(SDExp2–SDCon2), where SDExp and SDCon are the standard deviations of the change score (i.e., post – pre) in the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Some of the changes occurring after prolonged bedrest can persist for long after a return to normal activity (Trudel et al, 2009 ) and thus the system compromise from such deconditioning can be protracted even when reinstitution of physical activity is implemented. However, similar to space flight, the responses to bedrest can show considerable individual variation (Fernandez-Gonzalo et al, 2021 ; reviewed in Scott et al, 2021 ).…”
Section: Bedrest “Deconditioning” On Earth Parallels That Of Space Flightmentioning
confidence: 99%
“…Some of the changes occurring after prolonged bedrest can persist for long after a return to normal activity (Trudel et al, 2009 ) and thus the system compromise from such deconditioning can be protracted even when reinstitution of physical activity is implemented. However, similar to space flight, the responses to bedrest can show considerable individual variation (Fernandez-Gonzalo et al, 2021 ; reviewed in Scott et al, 2021 ).…”
Section: Bedrest “Deconditioning” On Earth Parallels That Of Space Flightmentioning
confidence: 99%
“…Indeed, shorter and less pennate muscle fibres have been reported alongside reduced muscular strength following spaceflight ( Koryak, 2019 ) and bed rest ( Reeves et al, 2002 ; De Boer et al, 2008 ). Further evidence of the complexity inherent to muscle adaptations, are i) a preferential shift from type I to type II fibres observed following disuse ( Trappe et al, 2004 ), ii) the inter-individual variation reported in the literature ( Fernandez-Gonzalo et al, 2021 ; Scott et al, 2021 ), which also complicates the adjustment of muscle model parameters. For example, muscle fibre CSA and peak isometric fibre force ranged between 49%–106% and 30%–90%, respectively, across eight astronauts from a single study ( Fitts et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Astronauts can present with substantial muscular adaptations, such as atrophy and reduced strength, power, and endurance, in as little as 7–14 days of spaceflight ( Winnard et al, 2019 ). To complicate matters, substantial inter-individual variability has been reported in the literature ( Fernandez-Gonzalo et al, 2021 ; Scott et al, 2021 ), both in terms of the magnitude and the nature of the muscular adaptations experienced by astronauts. For example, Widrick et al (1999) reported a 2-fold variation in responses of muscle contractile properties following 17 days spaceflight.…”
Section: Introductionmentioning
confidence: 99%